CLOUD SERVICE MODELS: A COMPREHENSIVE ANALYSIS OF INTEGRATION, STORAGE, AND ORCHESTRATION PARADIGMS - Anshul Goel (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
This article presents a comprehensive examination of cloud service models and their transformative role in modern computing environments. The article explores the fundamental architecture and characteristics of Infrastructure as a Service (IaaS), Platform as a Service (PaaS), and Software as a Service (SaaS), analyzing their integration patterns, storage solutions, and orchestration mechanisms. Through detailed investigation of component decoupling, event-driven systems, and containerization technologies, the research highlights critical strategies for achieving scalability and resilience in cloud deployments. The analysis extends to emerging applications in autonomous systems, Internet of Things (IoT), blockchain services, and recommendation systems, demonstrating the versatility and potential of cloud computing paradigms. Special attention is given to performance optimization techniques, data architecture considerations, and analytics integration, providing insights into effective cloud implementation strategies. The article also addresses crucial challenges in systems integration, security considerations, and future trends, offering valuable perspectives for organizations navigating their cloud transformation journey. The article underscore the significant impact of cloud computing on IT infrastructure modernization and its role in enabling digital transformation across industries.